The numerical evaluation of the grinding process and the basic mechanics of grinding wheel wear - Purcell, John (College of Aeronautics, 1965)
During the production process development for the manufacture of an experimental supersonic aircraft , an unusual and difficult grinding problem was encountered. Arising from the experimental work carried out to solve this problem, a method of numerically evaluating the efficiency of grinding wheels and coolants, was developed. This evaluation is based on the fact that under constant and limited grit load conditions which can be set up in a surface grinding operation, the edge of the grinding wheel which makes initial contact with the workpiece breaks down and forms an approach angle as shown in Fig. 1. Once this angle is established, its dimensions remain almost constant, and with continued use of the wheel the angle recedes across the face of the wheel. It is the recognition of the variables which control the dimensions of this approach angle (alpha) together with the rate at which it recedes across the wheel face, and the amount of work done at each increment of recession, on which the numerical evaluation of the efficiency of the grinding wheel and the causes of the limitations are based. A description of the methods used for determining the characteristics of grinding wheels and coolants are included together with the calculations which are necessary when the data obtained from tests carried out on the surface grinding machine are to be interpreted and applied to the cylinder grinding internal grinding or form grinding processes.